Physiological and electrophysiological characteristics of continuously cropped Pinellia ternata and a novel electrical information-based monitoring approach for its cropping obstacles - Zhang, Cheng; Liu, Jing; Wang, Zelan; Lu, Xiaona; Dai, Liangyu; Tang, Chenglin; Hang, Ye; Tian, Bing (Frontiers in Plant Science, 2025)
Continuous cropping obstacles drastically inhibit plant growth, medicinal composition, and tuber productivity of Pinellia ternata, thereby restricting its industrial development. There are few systematic reports on the physiological and electrophysiological responses of P. ternata under continuous cropping beyond 2 years, and effective obstacle monitoring methods remain undeveloped. Based on the results, continuous cropping for 1~4 years clearly inhibited morphological development, emergence rate, photosynthesis, antioxidant enzyme activities, and medicinal composition of P. ternata, while increasing its sprout tumble rate and resistance-related substance contents, as well as reducing tuber yield by 23.84%~59.20%. Meanwhile, continuous cropping could dramatically inhibit its intracellular water metabolism, nutrient transport, metabolic activity, and intrinsic capacitance (IC), while increasing its intrinsic resistance (IR), impedance (IZ), inductive reactance (IXL), and capacitive reactance (IXc). Additionally, these inhibiting or promoting effects intensified with the increasing duration of continuous cropping. Reliably, the comprehensive growth index (CGI) and continuous cropping obstacle index (CCOI), based on the plant’s electrical information, exhibited good correlations with the physiological and electrophysiological parameters, which accurately and rapidly characterized the growth and continuous cropping obstacle status of P. ternata. This study systematically described the physiological and electrophysiological characteristics of P. ternata under perennial continuous cropping, developed a novel monitoring approach based on the plant’s electrical information, and provided new insights for monitoring and mitigating its continuous cropping obstacle.